Set-recovery of heat treated maritime pine wood prior and after compression - Esteves, B. (2015)
Pine (Pinus pinaster) wood samples were subjected to a combined densification and heat treatment process. Samples were densified before and after heat treatment. The heat treatment was carried out inside an oven at 190ºC for 2 to 6 h and wood densification was performed in a hot press at around 48 bar pressure and at temperatures of between 160ºC and 200ºC for 30 min. Compression rate and density were determined after the treatment. Set recovery was determined by thee cycles of water soaking followed by oven drying. The best results were attained when densification was done before heat treatment. The set recovery was less than 30% for the first two cycles and a little higher in the third cycle. For wood treated for 6 hours, the set recovery was less than 15%. Heat treatment before densification seems to be less effective than after densification to enable set-recovery.